Comparative assessment of phytochemical profiles, antioxidant and antiproliferative activities of Sea buckthorn (Hippophaë rhamnoides L.) berries - Guo, Ruixue; Guo, Xinbo; Li, Tong; Fu, Xiong; Liu, Rui Hai (Food chemistry, 2017)
•Evaluated the phytochemical composition in four Sea buckthorn subspecies.•Compared in vitro and cellular antioxidant activities of phytochemical extracts.•Analyzed antiproliferative activity of phytochemical extracts and components.•Correlated of main effective composition with bioactive activities in Sea buckthorn. Phytochemical profiles, antioxidant and antiproliferative activities of berry extracts were evaluated and compared in four subspecies of Sea buckthorn (Hippophaë rhamnoides L.). Among the subspecies, Hippophaë rhamnoides L. subsp. sinensis exhibited highest total phenolics content (38.7±1.3mgGA equiv./g DW) and corresponding total antioxidant activity. Whereas maximum cellular antioxidant and antiproliferative activities were determined in Hippophaë rhamnoides L. subsp. yunnanensis. Total antioxidant activity was significantly associated to total phenolics, isorhamnetin-3-rutinoside and isorhamnetin-3-glucoside. The cellular antioxidant activity and antiproliferative activity of phytochemicals were fairly correlated to phenolic acids and flavonoid aglycones. Lower median effective dose (EC50) of individual compounds against human liver cancer HepG2 cells proliferation studies confirmed the better correlation between antiproliferative activity of Sea buckthorn extracts and flavonoid aglycones, including isorhamnetin, quercetin and kaempferol.